SHG for Women’s- Contribution to Economic Development (International Journal of Innovative Research in Engineering & Management, 2023)
The key to a nation's steady growth is the  empowerment of women. In terms of this, the self-help  group has a significant influence on how women are  empowered in rural areas. SHG works to strengthen the  socioeconomic conditions of the community's most  vulnerable members, which supports the nation's overall  economic development. This review article provides a  thorough overview of the SHG's achievements in  Prayagraj, Uttar Pradesh's Chaka Block with regard to  women's empowerment. Nearly all of the research reveals that SHG participants and  decision-makers in the democratic, economic, and social  realms of life acquire equality of status. This article also  offers some suggestions for how to implement SHG  successfully. Simple statistical tools were used in this  investigation. Based on an analysis of women's  empowerment over self-help groups, the primary results of  this study are that self-help groups have a constructive impact on women's empowerment in the Chaka Block.
Keywords: Self-Help Groups; Women Empowerment; SHG Movement; Socio-Economic Development